Lipid-lowering pretreatment and outcome following intravenous thrombolysis for acute ischaemic stroke: a post hoc analysis of the enhanced control of hypertension and thrombolysis stroke study trial - Minhas, Jatinder S.; Wang, Xia; Arima, Hisatomi; Bath, Philip M.W.; Billot, Laurent; Broderick, Joseph P.; Donnan, Geoffrey A.; Kim, Jong S.; Lavados, Pablo M.; Lee, Tsong-Hai; Martins, Sheila Cristina Ouriques; Olavarría, Verónica V.; et al. (Karger Publishers, 2018)
Background: Debate exists as to whether statin pretreatment confers an increased risk of 90-day mortality and symptomatic intracranial haemorrhage (sICH) in acute ischaemic stroke (AIS) patients treated with intravenous thrombolysis. We assessed the effects of undifferentiated lipid-lowering pretreatment on outcomes and interaction with low-dose versus standard-dose alteplase in a post hoc subgroup analysis of the Enhanced Control of Hypertension and Thrombolysis Stroke Study. Methods: In all, 3,284 thrombolysis-eligible AIS patients (mean age 66.6 years; 38% women), with information on lipid-lowering pretreatment, were randomly assigned to low-dose (0.6 mg/kg) or standard-dose (0.9 mg/kg) intravenous alteplase within 4.5 h of symptom onset. Of the total number of patients, 615 (19%) received statin or other lipid-lowering pretreatment. The primary clinical outcome was combined endpoint of death or disability (modified Rankin Scale scores 2–6) at 90 days. Results: Compared with patients with no lipid-lowering pretreatment, those with lipid-lowering pretreatment were significantly older, more likely to be non-Asian and more likely to have a medical history including vascular co-morbidity. After propensity analysis assessment and adjustment for important baseline variables at the time of randomisation, as well as imbalances in management during the first 7 days of hospital admission, there were no significant differences in mortality (OR 0.85; 95% CI 0.58–1.25, p = 0.42), or in overall 90-day death and disability (OR 0.85, 95% CI 0.67–1.09, p = 0.19), despite a significant decrease in sICH among those with lipid-lowering pretreatment according to the European Co-operative Acute Stroke Study 2 definition (OR 0.49, 95% CI 0.28–0.83, p = 0.009). No differences in key efficacy or safety outcomes were seen in patients with and without lipid-lowering pretreatment between low- and standard-dose alteplase arms. Conclusions: Lipid-lowering pretreatment is not associated with adverse outcome in AIS patients treated with intravenous alteplase, whether assessed by 90-day death and disability or death alone.